Bioaccumulation, distribution and elimination of chlordecone in the giant freshwater prawn Macrobrachium rosenbergii: Field and laboratory studies. (October 2017) - Lafontaine, Anne; Gismondi, Eric; Dodet, Nathalie; Joaquim-Justo, Célia; Boulangé-Lecomte, Céline; Caupos, Fanny; Lemoine, Soazig; Lagadic, Laurent; Forget-Leray, Joëlle; Thomé, Jean-Pierre
Abstract: Chlordecone is a persistent organochlorine pesticide that has been widely used in Guadeloupe (French West Indies) to control the banana weevil Cosmopolites sordidus from 1972 to 1993. A few years after its introduction, widespread contamination of soils, rivers, wild animals and aquatic organisms was reported. Although high chlordecone concentrations have been reported in several crustacean species, its uptake, internal distribution, and elimination in aquatic species have never been described. This study aimed at investigating the accumulation and tissue distribution of chlordecone in the giant freshwater prawn Macrobrachium rosenbergii, using both laboratory (30 days exposure) and field (8 months exposure) approaches. In addition, depuration in chlordecone-free water was studied. Results showed that chlordecone bioconcentration in prawns was dose-dependent and time-dependent. Moreover, females appeared to be less contaminated than males after 5 and 7 months of exposure, probably due to successive spawning leading in the elimination of chlordecone through the eggs. Chlordecone distribution in tissues of exposed prawns showed that cephalothorax organs, mainly represented by the hepatopancreas, was the most contaminated. Results also showed that chlordecone was accumulated in cuticle, up to levels of 40% of the chlordecone body burden, which could be considered as a depuration mechanism since chlordecone is eliminated with the exuviae during successive moults. Finally, this study underlined the similarity of results obtained in laboratory and field approaches, which highlights their complementarities in the chlordecone behaviour understanding in M. rosenbergii . Highlights: Chlordecone was accumulated in M. rosenbergii from the first hours of exposure. Chlordecone was mainly accumulated in hepatopancreas. Chlordecone was also found in cuticle tissue (up to levels of 40%). Depuration process of chlordecone was slow (∼94 days to reach the MRL).